Evil Spirit dalam Metode Keraguan Rene Descartes: Evil Spirit in Rene Descartes' Method of Doubt - Yudan, Fhikri Fhutera; Naupal, Naupal (Undiksha, 2025)
The advancement of digital technology and artificial intelligence (AI) has opened significant opportunities for accessing information but also poses serious threats in the form of misinformation and disinformation, raising the question: how can truth be ensured amidst the overwhelming flood of information humans face daily? In this context, Rene Descartes' method of doubt, with his concept of the evil spirit, offers a relevant reflective approach. This study employs a descriptive qualitative method using literature review techniques and critical reflection on primary and secondary sources. The concept of the evil spirit is a hypothetical scenario depicting an intelligent and malevolent entity capable of deceiving human senses and beliefs. This concept serves as a psychological and epistemological foundation in Descartes' method of doubt, enabling radical skepticism of sensory experiences. The study finds that Descartes' method of doubt not only supports the pursuit of philosophical truth but is also relevant as a critical tool for filtering information and addressing epistemological challenges in the digital era.